THE FIRST CLINICAL EXPERIENCE IS INTRAOPERATIVE STRETCHING OF THE SKIN IN THE ELIMINATION OF SCAR DEFORMITIES OF THE UPPER EXTREMITIES - Teshaboev M.G; Sulaimanova H.H; Parpiev A.L; Oripov D.U (Western European Studies, 2023)
The authors present the first clinical experience of using a new method of plastic surgery to eliminate the effects of burns of the upper extremities. 26 patients were operated on in a new way. The proposed method of upper limb plastic surgery with intraoperatively stretched tissues in 24 (92.3%) patients out of 26 allowed to achieve good functional and aesthetic results.
Keywords: surgical tactics; scar; scar deformation